Impact of Mobile Phone Usage on Behavioral Change of Rural Youth in India - A Cross-Sectional Analysis - R. Manikandan, (International Journal of Engineering and Management Research, 2023)
The study was taken up among the rural youths in the age group of 15-35 to find out the impact of mobile phone use on their behavioral changes in Salem District of Tamil Nadu. The study was based on primary data. Five demographic variables such as age, gender, marital status, family size and education were used as background variables to understand their inter-relationship between them. One common finding emerged from the background variables that the majority of mobile phone users were unmarried and school and college going students. To determine the impacting factors on behavioral changes due to more use of mobile phones, factor analysis was used. The factor analysis was clearly indicated psychological factors (stress, anxiety and depression) attributed to more use of mobile phone followed by increasing possibility of health hazards like non-communicable diseases and sedentary behavior on behavioral changes of respondents. Therefore, it is understood that the mobile phone usage can cause behavioral changes of the age group between (15-35), as this group prone to accept anything without understanding the long-term effects. Although mobile phone has become an integral part of daily life, it cannot be avoided but its judicial use could overcome some of its negative effects.